New technologies and education in the field of cultural heritage. «Madrid Industrial, Itineraries». An example of m-learning applied to industrial heritage - Francisco David de la Peña Esteban; Carmen Hidalgo Giralt; Antonio J. Palacios García (Centro de Estudios Financieros, 2015)
The development of the information and communication technologies (ICT), integrated within the current knowledge society, has transformed the way in which the human being relates to its environment. The integration of internet on mobile devices is one of the most representative cases on this matter. The universalization of smartphones has allowed not only to amplify the interpersonal communication but also explore new scenarios previously unsuspected. The application of mobile technologies to the education, which has been defined as m-learning, is breaking schemes of the traditional binominio teaching and learning to articulate pillar more dynamic as immediate access to knowledge, collaborative work or personalized learning. As a result of the numerous m-learning applications, it was considered appropriate to focus this research in the field of heritage education. That's why an application (app) for mobile that allows to interpret a cultural itinerary articulated in the industrial heritage of Madrid has been designed. The objective of this study consists of analysing how changes the app user's perception of the industrial heritage after finishing the route in order to get results that allow design educational projects of and implement more effective cultural policies.